Interventional Study on the Effectiveness of Eye Exercises Based on Composite Feedback Model in School-Age Children - Chen X; Zuo S; Zhang C; Sun B; Zhang M; Jiang D; Chen Y (Dove Medical Press, 2024)
Xiaojun Chen,1,* Shushu Zuo,1,* Chunhua Zhang,1 Bing Sun,1 Mengyue Zhang,1 Dandan Jiang,2 Yanyan Chen2 1School of Optometry and Ophthalmology, Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People's Republic of China; 2National Clinical Research Center for Ocular Diseases, Eye Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, 325027, People's Republic of China*These authors contributed equally to this workCorrespondence: Yanyan Chen; Dandan Jiang, National Clinical Research Center for Ocular Diseases, Eye Hospital, Wenzhou Medical University, No. 270, Xueyuan West Road, Lucheng District, Wenzhou, Zhejiang, 325027, People's Republic of China, Tel +86 13858855689 ; +86 13506649289, Email cyy@eye.ac.cn; jiangdandan@eye.ac.cnObjective: This study aims to explore the effects of eye exercises on the accommodative ability of Chinese school-aged children.Methods: This study used a convenience cluster sampling and selected 149 students from grades 2- 5 in a Wenzhou primary school to participate in the intervention in June 2022. This study involved a one-month intervention teaching eye exercises using a composite feedback model. Assessments were made at 3 and 9 months post-intervention. Data collection occurred thrice, including a baseline and two follow-ups, measuring monocular and binocular accommodative facility, monocular and binocular accommodative amplitude, CISS scale, spherical equivalent refraction, and uncorrected visual acuity. Analysis used chi-square tests and generalized estimating equations to evaluate the exercises' effectiveness, with a significance threshold of P < 0.05.Results: 134 students completed the follow-up, including 61 females (45.52%). After teaching intervention, students showed significant improvements in the accuracy of manipulation, rhythm, acupoint location, strength effectiveness and rhythm of acupressure eye exercises (all P < 0.05), with increases of 10.37%, 13.03%, 16.96%, and 25.17%, respectively. Follow-up assessments revealed both monocular and binocular accommodative amplitude at T3 were significantly higher than at T1 and T2. Moreover, the binocular accommodative amplitude in the high-quality eye exercise group remained significantly higher than that in the low-quality group even(B=1.39,1.46, P < 0.01). Eye exercises could improve monocular and binocular accommodative amplitude in the short term(P < 0.05). High-quality eye exercises could alleviate visual fatigue (B=− 2.00--3.49, both P < 0.05). However, eye exercises did not demonstrate any advantages in affecting spherical equivalent refraction or uncorrected visual acuity (P > 0.05).Conclusion: Eye exercises can alleviate myopia-related symptoms in Chinese children aged 7 to 11 years. However, this study did not find that eye exercises effectively reduce the degree of myopia in children.Trial Registration: The original trial (Registration site: https://www.chictr.org.cn/ Registration number: ChiCTR2300070903) was retrospectively registered on 26/04/2023.Keywords: Eye exercises, myopia, accommodative facility, accommodative amplitude, visual fatigue